Selective Esophagogastric Devascularization in the Modified Sugiura Procedure for Patients with Cirrhotic Hemorrhagic Portal Hypertension: A Randomized Controlled Trial - Yawu Zhang; Lingyi Zhang; Mancai Wang; Xiaoling Luo; Zheyuan Wang; Gennian Wang; Xiaohu Guo; Fengxian Wei; Youcheng Zhang (Canadian Journal of Gastroenterology and Hepatology)
Aim. Portal hypertension is a series of syndrome commonly seen with advanced cirrhosis, which seriously affects patient’s quality of life and survival. This study was designed to access the efficacy and safety of selective esophagogastric devascularization in the modified Sugiura procedure for patients with cirrhotic hemorrhagic portal hypertension. Methods. Sixty patients with hepatitis B cirrhotic hemorrhagic portal hypertension and meeting the inclusion criteria were selected and randomly divided by using computer into the selective modified Sugiura group (sMSP group, n = 30) and the modified Sugiura group (MSP group, n = 30). The primary endpoint measurement is the postoperative rebleeding rate. Secondary endpoint measurements included free portal venous pressure, liver Child–Pugh score, liver volume, portal vein width and blood flow velocity, survival rate, quality of life, and dysphagia as well as other complications one year postoperatively. This trial is registered with ChiCTR, number ChiCTR2000033468. Results. There was no statistically significant difference in rebleeding rates within one year after surgery between patients in the sMSP and MSP groups (χ = 0.11, p=0.73). In comparison with the MSP group, the Child–Pugh score of liver function in the sMSP group significantly increased (χ = 6.4, p=0.04) and the incidence of dysphagia was significantly reduced (χ = 6.23, p=0.01) one year after surgery. There was a statistically significant difference in the quality of life between the two groups. However, there were no statistically significant differences in free portal venous pressure (MD = −3.44, 95% CI: −7.87 to 0.98, p=0.12), postoperative liver volume (3 months: MD = -258.81, 95% CI: −723.21 to 205.57, p=0.24; 1 year: MD = −320.12, 95% CI: −438.43 to 102.78, p=0.16), postoperative portal vein width (3 months: MD = −0.06, p=0.50; 1 year: MD = 0.17, p=0.21), portal vein flow velocity (3 months: MD = 1.64, p=0.21; 1 year: MD = −1.19, p=0.57), 1-year survival rate (χ = 1.01, p=0.31), and other complications between the two groups. Conclusions. Selective esophagogastric devascularization in the modified Sugiura procedure may not lower the incidence of rebleeding in the short term based on our findings. However, it may significantly improve quality of life of patients with cirrhotic hemorrhagic portal hypertension, improve liver function, and reduce postoperative dysphagia.